Information behaviour and factors influencing family planning knowledge of Myanmar ethnic migrants: a qualitative study: 10.55131/jphd/2024/220103 - Ohn, Nan San Thidar; Worland , Shirley (Journal of Public Health and Development, 2023)
The accessibility to quality family planning (FP) information and counselling for Myanmar ethnic migrants in Thailand is questionable. Inadequate knowledge and lack of informed choice to practice FP methods increase the risk of unmet needs and method failures in FP, which could result in unplanned pregnancies and induced abortions. This research aimed to understand the FP information behaviour of a Pa-O migrant group, as well as structural and agency influencing factors on FP knowledge acquisition in Chiang Mai. A qualitative research based on the Information Behaviour model and Structuration theory was conducted using participant observation, in-depth interviews, focus group discussions, and key informant interviews. A non-probability sampling method was employed, and 31 respondents participated in the study. The study found that actively seeking FP information from formal sources to make an informed decision was not common among Pa-O migrants. Instead, there was more reliance on informal information sources for choosing FP methods. Cultural norms related to sex, marriage, and age hinder migrant health information-seeking behaviour from formal and informal information sources. Pa-O migrants were alienated from structural resources, limiting the opportunities to promote FP knowledge. The personal and situational factors that significantly influenced the agency of migrants were lack of awareness of the right to information, language barriers, and perceived communication barriers with health staff. Limited resources of migrant-friendly health education programmes adversely affect migrant FP information behaviour. Reproductive health education programmes, including quality FP counselling services, should be accessible for marginalised migrants to ensure that their choices of FP are well-informed.